A qualitative examination of injury prevention strategy and education in Ladies Gaelic football: Understanding the preferences of players and coaches. - John Corrigan; Sinéad O'Keeffe; Enda Whyte; Siobhán O'Connor (PLoS ONE, 2023)
The high rates of injury in Ladies Gaelic football impact the wellbeing of players and are a major financial burden for the Ladies Gaelic Football Association. Effective injury prevention programmes have been developed for Gaelic games, but these are not currently widely adopted. The aim of this study was to qualitatively investigate adult Ladies Gaelic football players and coaches' preferences for injury prevention strategies and injury prevention education using a constructivist grounded-theory approach. Semi-structured interviews were conducted with 23 currently active Ladies Gaelic football coaches and adult players. The core strategy preferences discussed by participants were the properties of an injury prevention programme, the role of stakeholders, strategy logistics and the need for guidance and support. If the uptake and long-term adoption of an injury prevention programme is to be maximised, the preferences of the players and coaches who will ultimately utilise the programme must be understood and integrated into a wider implementation strategy developed around their needs. For education preferences, the core categories identified were the focus of education, who needs education, the format, educator, roll-out strategy, and time required. Future educational strategies must incorporate the preferences of stakeholders into their design if they are to be successful in spreading injury prevention knowledge and achieving change. To give injury prevention strategies, programmes, and education the best chances at successful adoption, it is crucial that the preferences of end-users are addressed and implemented.